Individual and group preferences over risk: Does group size matter? - Andrea Morone; Francesco Nemore; Tiziana Temerario (Economics and Econometrics Research Institute (EERI), 2017)
In this paper we investigated group size impact on risk aversion when a majority rule is applied. Drawing on the widely used Holt and Laury's (2002) lottery pairs, we observed a risky shift for both individual and groups regardless of their size. However, groups choices are shown to be closer to the risk-neutrality prediction. More interestingly, whereas smaller groups attitudes can be safely approximated by individual choices, larger groups reveal a statistically different risk-loving attitude. This risky shift becomes more prominent as group size increases.
Keywords: C91; C92; D01; 330; Preferences; Group; Risk Attitude; Majority Rule; Laboratory